2022
DOI: 10.1038/s41598-022-09477-2
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty about others’ trustworthiness increases during adolescence and guides social information sampling

Abstract: Adolescence is a key life phase for developing well-adjusted social behaviour. An essential component of well-adjusted social behaviour is the ability to update our beliefs about the trustworthiness of others based on gathered information. Here, we examined how adolescents (n = 157, 10–24 years) sequentially sampled information about the trustworthiness of peers and how they used this information to update their beliefs about others’ trustworthiness. Our Bayesian computational modelling approach revealed an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 55 publications
7
31
0
Order By: Relevance
“…These studies have shown that preferences become clearer (less uncertain) across development 68 . Uncertainty also undergoes developmental change for instance when people decide whether to trust others or not 84 . Previously, it was shown in adults that uncertainty makes novel information more impactful during (social) learning [85][86][87] and drives exploration [88][89][90] .…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that preferences become clearer (less uncertain) across development 68 . Uncertainty also undergoes developmental change for instance when people decide whether to trust others or not 84 . Previously, it was shown in adults that uncertainty makes novel information more impactful during (social) learning [85][86][87] and drives exploration [88][89][90] .…”
Section: Discussionmentioning
confidence: 99%
“…Using a Bayesian updating model, the authors showed that participants changed their choice preference more often in the direction of the choice made by the other player in the uncertain versus the certain condition and when they were subjectively more uncertain within conditions. Moreover, a recent study in which adolescents had to decide whom to trust revealed an adolescence-emerging increase in uncertainty of prior beliefs, which accounted for differences in information sampling about others' trustworthiness ( Ma et al, 2022 ). In another study by Moutoussis and colleagues, a group of 14–24 year olds played a temporal discounting task in which they could choose between a smaller but immediate reward or a larger but delayed reward, and they indicated their preferences both before and after viewing the preferences of others ( Moutoussis et al, 2016 ).…”
Section: Informational Peer Influence In Adolescence: the Role Of Unc...mentioning
confidence: 99%
“…Note that this transition period delineated by the onset of pubertal changes has also been referred to as early adolescence (Holm et al, 2022;Pelham III et al, 2021). Our study focuses on this preadolescent phase, as it may represent a window of opportunity to increase prosocial behavior, positive social outcomes, and decrease the risk for poor health outcomes in adolescence (Flook et al, 2019;Ma et al, 2022). In this study, we aimed to characterize ongoing development underlying cooperation decisions, a key social behavior, in preadolescent children.…”
Section: Introductionmentioning
confidence: 99%
“…Children and adults have been shown to successfully gather information about a trustee's past behavior to minimize their uncertainty about the trustee's trustworthiness (Vives & Feldmanhall, 2018). Ma and colleagues (Ma et al, 2020(Ma et al, , 2022 assessed how adults and adolescents sequentially sampled information about a trustee's reciprocation history before making cooperation decisions. The authors found that both adolescents and adults sampled information about their partners to decrease uncertainty about their trustworthiness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation